Improved detection of right colon adenomas with additional retroflexion following two forward-view examinations: a prospective study - Lee, Hyun Seok; Jeon, Seong Woo; Park, Hye Yoon; Yeo, Seong Jae (Endoscopy, 2017)
Background and study aims Colonoscopy in the right colon is less effective than in the left colon in screening for colorectal cancer. The aim of this study was to prospectively evaluate the diagnostic value of retroflexion in the right colon.Patients and methods A total of 1020 patients undergoing screening or surveillance colonoscopy were enrolled. After the first cecal intubation, the scope was withdrawn from the cecum to the hepatic flexure in the standard forward view and all identified polyps were resected. A second examination from the cecum to the hepatic flexure was then performed in standard forward view, and finally a third examination of that same segment was conducted in retroflexion. Additionally detected polyps at each examination were removed. The main outcome measures included the proportion of procedures with successful retroflexion, the additional yield for adenoma detection, and the adenoma miss rate.Results Retroflexion was successful in 840 patients (82.4 %). Retroflexion detected a significantly greater proportion of patients with adenomas in the proximal segment than the two standard examinations combined (forward view 25.5 % vs. total examination 27.5 %; P < 0.001). The per-adenoma miss rate of the two standard examinations in the right colon was 10.4 % (52/502), and the per-patient adenoma miss rate was 4.9 % (50/1020). The detection of additional adenomas using retroflexion was associated with age ≥ 55 years, gastroenterologist experience, and the presence of polyps on forward-view examination.Conclusions Colonoscopic retroflexion in the proximal colon resulted in an increased detection of adenomas, even after two consecutive forward-view examinations.Trial registered at Clinical Research Information Service (CRIS): KCT0000725.